Optical Multiparameter Detection System Based on a Broadband Achromatic Metalens Array. Issue 19 (1st July 2021) - Feng, Xing; Wang, Yuxi; Wei, Yunxuan; Hu, Tie; Xiao, Shunyuan; He, Guangqiang; Zhao, Ming; Xia, Jinsong; Yang, Zhenyu
Abstract: Metalenses, known as flat metasurface lenses based on subwavelength phase modulations, have been widely applied to compact and multifunctional optical devices due to their high flexibility in controlling light. However, most metalenses only operate at single wavelength, limiting their practical applications. In this paper, an achromatic metalens array (AMLA)‐based optical multiparameter detection system, for a near‐infrared spectrum from 1310 to 1550 nm, is reported. Such system can simultaneously detect the spatially varying polarization and phase gradient of the broadband beam. Its performance is experimentally characterized at wavelengths of 1310, 1430, and 1550 nm. Average errors of 18 selected polarization states are respectively 6.40%, 6.74%, and 6.02%. Average errors of phase gradients of seven different incident light are 8.93%, 7.44%, and 5.68%. This system can find applications in structured light detection, quantum optics, and polarization imaging. Abstract : Here, an optical multiparameter detection system operating from 1310 to 1550 nm is demonstrated, which is based on an achromatic metalens array. Such system can simultaneously detect the polarization and phase gradient of the broadband beam. Its performances are experimentally characterized at the wavelength of 1310, 1430, and 1550 nm.